Dihydroartemisinin Exerts Antifibrotic and Anti-Inflammatory Effects in Graves’ Ophthalmopathy by Targeting Orbital Fibroblasts - Yang, Shenglan; Wang, Xing; Xiao, Wei; Xu, Zhihui; Ye, Huijing; Sha, Xiaotong; Yang, Huasheng (Frontiers in Endocrinology, 2022)
Graves’ ophthalmopathy (GO) is a common orbital disease that threatens visual function and appearance. Orbital fibroblasts (OFs) are considered key target and effector cells in GO. In addition, hyaluronan (HA) production, inflammation, and orbital fibrosis are intimately linked to the pathogenesis of GO. In this study, we explored the therapeutic effects of dihydroartemisinin (DHA), an antimalarial drug, on GO-derived, primary OFs. CCK8 and EdU assays were applied to evaluate the antiproliferative effect of DHA on OFs. Wound healing assays were conducted to assess OF migration capacity, while qRT-PCR, western blotting, ELISA, and immunofluorescence were used to determine the expression of profibrotic and pro-inflammatory markers in these cells. Moreover, RNA sequencing was conducted to identify differentially expressed genes (DEGs) in DHA-treated OFs, and Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analysis of DEGs was performed to explore potential mechanisms mediating the antifibrotic effect of DHA on GO-derived OFs. Results showed that DHA dose-dependently inhibited OF proliferation and downregulated, at the mRNA and protein levels, TGF-β1-induced expression of fibrosis markers, including alpha smooth muscle actin (α-SMA) and connective tissue growth factor (CTGF). Furthermore, DHA inhibited TGF-β1 induced phosphorylation of extracellular signal-regulated protein kinase 1/2 (ERK1/2) and signal transducer and activator of transcription 3 (STAT3), which suggested that DHA exerted antifibrotic effects via suppression of the ERK and STAT3 signaling pathways. In addition, DHA suppressed the expression of pro-inflammatory cytokines and chemokines, including IL-6, IL-8, CXCL-1, MCP-1, and ICAM-1, and attenuated HA production induced by IL-1β in GO-derived OFs. In conclusion, our study provides first-time evidence that DHA may significantly alleviate pathogenic manifestations of GO by inhibiting proliferation, fibrosis- and inflammation-related gene expression, and HA production in OFs. These data suggest that DHA may be a promising candidate drug for treatment of GO.